Hypoxia and the heart : the role of nitric oxide in cardiac myocytes and endothelial cells - Strijdom, Hans (Stellenbosch : University of Stellenbosch, 2007)
Thesis (PhD (Biomedical Sciences. Medical Physiology))--University of Stellenbosch, 2007.